Комісія словника живої української мови у справі СВУ: Андрій Васильович Ніковський - Тищенко, О.М. (Мовознавство, 2019)
У статті досліджено позамовні й позамовознавчі умови, у яких виформовувалася національна ідентичність української лексикографії п. п. ХХ ст., зокрема звернено увагу на діяльність Комісії для складання Словника живої української мови через призму справи Спілки визволення України, через особистості авторів «Російсько- українського словника» (1924–1933) як учасників процесу, а саме А. В. Ніковського. Присвячено 100-річчю початку роботи над академічним «Російсько-українським словником» за ред. А. Ю. Кримського та С. О. Єфремова 1924–1933 рр. To the 100-th anniversary of the beginning of work on the academic «Russian- Ukrainian dictionary» edited by А. Crimskiy and S. Yefremov 1924–1933 (RUD). The article focuses on the work of the Living Ukrainian Dictionary Commission in the case through the prism of the case ULU (the Union of Liberation of Ukraine), through personalities of authors of Dictionary as participants of the process. Exactly this academic group in the Institute of Ukrainian Scientific Language Sciences Academy of Ukraine was «appointed» the center of ULU in the Academy, and S. Yefremov — the head of the «hostile» organization. In the context of research of the RUD it is expedient to study lingual and linguistic, extralingual and extralinguistic factors, the conditions in which the national identity of the Ukrainian lexicography of the early twentieth century was formed. In the declassified archives of the Security Service of Ukraine, materials of the process of ULU are stored, among which there are cases of three members of the Living Ukrainian Dictionary Commission: H. Holoskevych, A. Nikovskiy and S. Yefremov. This article will discuss the Living Ukrainian Dictionary Commission through the prism of the case Andrii Nikovsky. It was once again confirmed: to be an enemy to the Soviet power, it was enough merely to love nation and have the dignity to work for her self-affirmation.